Multisectoral Nutrition Assessment in Sri Lanka's Estate Sector - World Bank Group (Washington, DC: World Bank, 2017)
This Multisectoral Nutrition Assessment assessed the nutrition situation amongst residents of the estate sector, identified the main causes of nutritional deficiencies, as well as gaps in the provision of key nutrition-related services. The findings and recommendations can be used to inform policymakers and planners who are preparing the Estate Health Strategic Policy and Plan, and thereby implement effective multisectoral nutrition and health interventions. To this end, the two main objectives of the study were to: i) Assess the size, severity, and key determinants of undernutrition in Sri Lanka's estate sector. ii) Examine residents' access to—and utilization of nutrition related services and identify the gaps, if any, in institutional and implementation arrangements.The report is organized into six chapters. Chapter second presents the methodology employed (data and framework), Chapter third gives an overview of nutritional status in the estate sector, focusing particularly on maternal and child nutrition. Using a modified UNICEF conceptual framework, Chapter fourth explores the key immediate as well as underlying and basic determinants of undernutrition. Chapter fifth reviews the degree to which nutrition is positioned in the national development agenda and discusses gaps in current nutrition specific and nutrition-sensitive programs, and the last chapter outlines recommendations for the way forward.